Kajian Karakteristik Penggunaan Pelepah Pisang Sebagai Bahan Komposit Pelapis Rumah Blender Untuk Menurunkan Kebisingan Blender - Jefri Arianto; Sutrisno, Franky; Tony Siagian (CV. IRA PUBLISHING, 2022)
The problem of noise exists in our living environment both inside and outside the house and many people are not aware of the consequences of this noise even though they experience discomfort. Noise is an unwanted sound by humans because it can interfere with human hearing, especially those caused by electrical appliances in the kitchen such as blenders. The purpose of this study was to determine the effect of using banana midrib as a composite material for coating a blender housing to reduce noise. The research method is carried out by testing the impedance tube of the composite material sample with fine banana midrib fiber with a mesh diameter of ± 1 mm and a coarse sample of 2 mm to 5 mm, and also measuring sound level with sound absorption at the initial noise level of the room 41 dB. with a distance of 1 meter and a time multiple of 3 seconds for 2 minutes. The results of this study showed that the banana midrib coating had a 3% decrease for the no-load coating and a 2% decrease for the load-bearing coating.